Evaluation of Compressive Strength of Concrete with Various Proportions of Stone Dust as Fine Aggregate - Malla, Aashis; KC, Narayan; Aryal, Rajendra; Joshi, Buddhi Raj (Himalayan Journal of Applied Science and Engineering, 2024)
Concrete is the most dynamic engineering material in construction due to its durability and strength properties, which have been used in almost all types of physical infrastructure construction. Crushed stone dust is a supplementary material that can be utilized to produce sustainable concrete. The concept of replacing natural fine aggregate in concrete production with stone dust (SD) could enhance the consumption of stone dust produced during aggregate production as well as reduce the requirement for landfill area for stone dust management. The study aims to compare the compressive strength of nominal mixed M20 and M25-grade concrete by replacing fine aggregates with stone dust. The results reveal that compressive strength increases with an increase in stone dust, but the rise in SD percentages beyond a certain level has a negative impact on the strength of concrete. However, fresh density has a similar trend of compressive strength, and the workability of concrete shows a declining trend with a rise in SD levels. From the results of the experimental investigations conducted, it is concluded that the SD can be used as a replacement for fine aggregate. It is found that 40% replacement of fine aggregate by SD gives a maximum compressive strength than normal M20 and M25 grade concrete, which starts decreasing beyond 40% replacement. The compressive strength of the concrete has been quantified by replacing sand with varying percentages of stone dust and found that it does not satisfy the specification except for 40% replacement for M20 grade concrete, though it can be used for low and medium strength concrete production. The cost savings for M20 and M25-grade concrete at 40% sand replacement are 8.23% and 7.62%, respectively.